2021
DOI: 10.1007/s10643-021-01275-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Young Children’s Social Interactions During Digital Play

Abstract: In digital play, social interactions have aroused much debate among early childhood stakeholders, particularly in the areas of young children’s social learning and their domains of development. The main concern of early childhood educators is the limits of children’s social interactions occurring in digital play. This study used a four-week semi-structured field observation of eighty 3–4-year-old children within three Australian childcare centres to investigate children’s social interaction whilst involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For this reason, digital gaming is accepted as a form of gaming. Unlike traditional play activities, digital play was defined as a context in which children use digital technologies [8]. Recently, a growing interest has been in investigating the link between digital games and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, digital gaming is accepted as a form of gaming. Unlike traditional play activities, digital play was defined as a context in which children use digital technologies [8]. Recently, a growing interest has been in investigating the link between digital games and children.…”
Section: Discussionmentioning
confidence: 99%
“…Nevski and Siibak [6] defined digital play as the actions children perform on the touch screen, while Kinzie and Joseph [7] defined it as fun and exciting actions where the rules are followed in line with a goal. In short, digital play is expressed as an area where children use digital technologies [8]. Based on these definitions, it is seen that digital games include learning through exploration and inquiry, as well as learning through play in a broader context.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of electronic devices, children demonstrated high levels of engagement during digital play. Electronic books with thoughtful enhancements, such as animated pictures, music, and sound effects support children to engage in content learning and may inspire them to diversify different forms of play [ 36 , 37 ]. However, there is a caveat of electronic devices as children’s mental effort may be focused on interacting with the features rather than paying attention to their parents and surroundings [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with ongoing debates in other studies between the benefits and risks of screen time on child development. Some research has shown that electronic devices can help children learn and develop [54,55]. However, constant stimulation and absorption of visual content on screens have also been shown to impact young children's focus and concentration [56].…”
Section: Discussionmentioning
confidence: 99%